The Perspective of Consumers in Vientiane, Laos PDR, toward the Thai Shopping Mall in the Border Area, Nongkhai Province, Thailand, y Factor Analysis Technique - Kittimetheekul, Nara; Vongsanga, Niddavone; Lomchanthala, Phanphasa; Keorodom, Boutsakhone (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research was an empirical research that aimed to analyze the factors and components of the Laos consumers’ from Vientiane attitudes toward the shopping mall in Nong Khai province, Thailand. The research tool was a closed-ended questionnaire to measure the attitudes with a 5 level Likert Scale. The data collection used 221 answered questions from 19 variables using random sampling by the convenient method. The data was analyzed by the factor analysis technique. The results found that the factors relating to the Lao customers’ perspective were different from the marketing mix principle. There were five customer perspective; 1) the cost to the customer, 2) the physical touch point,3) customer safety, 4) emotional enhancement and 5) lifestyle. The five factors consisted of seventeen variables. However, the facility convenience variable, and promotion variable could not be matched with any other factors.